Politik Hukum dalam Reformasi Sistem Peradilan di Indonesia - Agung, I Gusti Agung Ngurah; Kusuma, Tiyar Cahya Kusuma; Pranacitra, Resi; Anggawira, Anggawira (HUMANIORUM, 2024)
The reform of Indonesia's judicial system is part of the ever-evolving legal political dynamics driven by public demands for greater transparency, accountability, and justice. Legal politics plays a strategic role in shaping the direction of judicial reforms, both in policy formation and implementation. Various factors, including legislation, political pressure, social influences, and economic conditions, contribute to this reform process. This article examines the role of legal politics in Indonesia's judicial reform by highlighting the factors influencing policy development and the challenges in its implementation. Using a normative juridical approach, this study analyzes post-reform legal policies, including regulatory changes and judicial institution restructuring, as well as their impact on the effectiveness and credibility of the judiciary. This study aims to provide a deeper understanding and recommendations to enhance the quality of the judicial system in the future.